?stanbul Housing and Land Appraisal System Reform Development Process and Property Values Analysis - Pelin Yigit (International Journal of Formal Sciences: Current and Future Research Trends, 2023)
One of the main problems of developing countries is having difficulties in finding sources for housing finance. In order to solve housing finance problems of a country, institutional systems that have been structured according to its own economic and social conditions should be applied by the government. The main purpose of this study is to determine an appropriate housing finance development designed based on Turkey’s current conditions. In this study, the location of the construction sector in Turkey’s economy, development of real estate sector in Turkey, the embryonic period of the housing market, development of criteria and indicators in the housing sector reform in the housing system were investigated. The construction sector is a so-called locomotive instruction of the economy. Turkey in the building industry as one of the economies in this category, especially after the 1980s and is growing constantly evolving. Today, the real estate sector has entered a rapid development process. Importance has been given to user needs in the projects produced and marketability has started to be seen as one of the most important factors of project success. For the solution of the housing problem, all the legal and operational measures taken by the state and the priorities determined are called housing policy. If the housing policy concept is to be examined, how the housing becomes a field of policy-making, how housing policies manifest in developed and underdeveloped countries or the problems encountered in its formation and performance can be studied and explored separately. Housing problems, housing policy and examine engaments held in Turkey on a private housing finance field are reached some conclusions. The first one is the fact that the housing problem is a dynamic structure and may vary periodically in Turkey as it is in the world due to changes in demographic structure, stock depreciation and migration. Second, it is compulsory that the issue of housing as an economic asset increases with the globalization of the world, and that it is necessary to address this issue more carefully in countries that are in the process of transition to global economic integration. Third, the rapid population growth in Turkey (albeit with a relatively slow) will continue in the coming 20-year period together with urbanization, especially the aging of the stocks that make up the majority mania apartment blocks began in 1950-1960’s year, worn with together will increase the destruction. A housing policy that is designed with these principles in mind; Financial Interventions to be carried out on housing investments, taxes, loans, housing purchase methods and similar areas, rent control and condominium applications, legal interventions to be carried out on various legal restrictions and incentives and housing standards, housing production types, construction methods and building materials technical interventions. At the end of this study, it is understood that housing finance model based on mortgage backed securities can be applied in the near future in Turkey. However, there are some requirements and regulatory needs must be fulfilled in many fields, such as in law of bankruptcy, tax regulations, law of banking and leasing, capital markets, and real- estate appraisal applications.